Pengaruh Kompetensi, Motivasi, dan Kepemimpinan terhadap Efektivitas Kerja - APRIANI, FAJAR (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2011)
The role of lecturers, as a professional force appointed legally in Higher Education, has three major functions, i.e. education, research, and contribution to society—known as Tridharma Perguruan Tinggi (The Three Principles of Higher Education). Considering the importance of the lecturers’ position, role, and function as educational force in higher education, we need to be consistent in implementing Tridharma Perguruan Tinggi in order to achieve the goal of improving the quality of our human resources. The research aims to examine the influence of competence, motivation, and leadership toward the effectiveness of the implementation of Tridharma Perguruan Tinggi by the lecturers in Mulawarman University. The result of the research shows that competence, motivation, and leadership are strongly and significantly related to the implementation of Tridharma Perguruan Tinggi by Mulawarman University’s lecturers.